Quantitative single-molecule analysis of assembly and Ca2+-dependent disassembly of synaptotagmin oligomers on lipid bilayers - Feng Li; Jeff Coleman; Lorena Redondo-Morata; R. Venkat Kalyana Sundaram; Ekaterina Stroeva; James E. Rothman; Frédéric Pincet (Communications Biology)
Abstract Synaptotagmin-1 (Syt-1) self-assembles into ring-like oligomers, and genetic and biochemical evidence suggest that oligomerization is needed to clamp synaptic vesicles and stabilize them for Ca2+-evoked release. However, oligomerization has not yet been demonstrated on lipid bilayers or studied in quantitative biophysical terms. Here we utilize single-molecule imaging methods to monitor the assembly and disassembly of oligomeric clusters of Syt-1 on lipid bilayers in real-time. Syt-1 assembled into two distinct classes of oligomers, small (5 ± 2 subunits) and large (15 ± 2 subunits). Each class assembled at a constant k on that was always proportional to its ultimate size, but both classes disassembled at the same unit rate (k off ) independent of its size. Both large and small oligomers explosively disassembled when Ca2+ was added. The F349A mutation in the Syt-1 nearly eliminates the large class of oligomers but does not reduce the small class. Altogether, the physical-chemical properties of Syt-1 oligomers meet or exceed the physiologic requirements to function as such a clamp.